In vitro and in vivo models to assess cancer metastasis - Amaral, Maria Constança Gomes Redinha Pais do (2017)
Cancer metastasis is the major cause of cancer-related deaths. Some proteins/lipids-attached glycans are aberrantly expressed in cancer and this pattern is highly associated with malignancy and tumor progression. Thus, aberrant glycans are promising candidates as cancer biomarkers and therapeutic targets. Glycosyltransferases overexpression is the main mechanism behind tumor-associated glycans such as Sialyl-Tn (STn), α2,6-sialyl lactosamines and Sialyl Lewis X (SLex) antigens. Colorectal cancer (CRC), the second most common cancer, is described to present STn and SLex, which correlate with disease progression. Although no glycan biomarkers yet reached clinical application due to the scarce understanding of the molecular mechanisms and the lack of relevant in vitro/vivo models to address them. Therefore, this study main goal was to establish experimental models of CRC cell lines expressing altered glycans and to evaluate their behavior in vitro through: CRC cell lines 1) overexpressing STn and 2) expressing Luciferase. In the first, the LS174T cell line was transduced with ST6GALNaC I gene to induce STn expression. In the second, SW48, SW948, SW620 and HT29 cell lines that overexpressed, or not, relevant sialyl and fucosyltransferases were used: ST6Gal 1 responsible for increased α2,6 sialylation; and FUT 6, responsible for increased SLex expression. These cell lines were then genetically modified to express LUCIFERASE (LUC) gene to allow cell tracking. After ST6GALNaC I or LUC genes transduction, the cells were phenotyped by flow cytometry to assess glycan expression and Luciferase was assessed by bioluminescence. Results showed that LS174T did not induce STn expression after transduction, since its precursor was absent. Regarding the remaining cell lines transduced with LUC, only HT29 FUT VI and SW948 ST6GAL I, and respective controls, emitted bioluminescence when tested. This study contributed to the comprehension of cancer-related glycan expression in CRC cell lines. These established cell lines may open the way for future investigation lines of metastasis development in vivo.